Disenfranchised narratives. Slavoj Žižek reads Jorge Semprún. Issue 3 (3rd July 2021) - Pabst, Stephan
ABSTRACT: Taking a critical approach to Slavoj Žižek's reading of Jorge Semprún's novel Le Grand Voyage, the paper treats Žižek's observations as being exemplary of a historically inexact usage of the term Holocaust (Literature) that strives to underpin the claims made by a normative poetics of Modernism by implying the existence of a more or less unquestionable interrelationship between Modernism and the Holocaust (experience) that hinges upon the idea of 'trauma.' Reconstructing the political experience behind – and the political ethics prevalent in – Semprún's novel, the paper sets out to question this particular line of reasoning.